Can vitamin supplementation improve quality of life and disease severity in patients with rheumatoid arthritis, or is physical activity enough? - Michał Andrzej Kozicz; Paulina Cuper; Ilona Jastrzębska; Krzysztof Bilecki; Hubert Gugulski; Michał Bado; Patrycja Nowoświat; Michał Goncerz (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by inflammation and progressive joint destruction, significantly impacting quality of life. While conventional treatments focus on managing symptoms and slowing disease progression through pharmacological means, the potential role of complementary therapies like vitamin supplementation or increased physical activity has garnered increasing interest. Aim of the Study: This narrative review explores the existing literature on the efficacy and mechanisms of various vitamins in the management of RA. By synthesizing current research findings, we aim to provide a comprehensive overview of how vitamin supplementation might influence RA outcomes, offering insights into potential integrative approaches to enhance patient care. Methods and Materials: A thorough search was conducted using PubMed and Google Scholar, focusing on literature published in the past five years. Vitamins with potential impacts on RA progression were identified and paired with the term "Rheumatoid Arthritis" to collect data on their influence on the disease's incidence and management, as well as the mechanisms involved. Additionally, references from selected articles were reviewed and included in the analysis. This method ensured a comprehensive evaluation of the current evidence regarding vitamin supplementation in RA treatment. Similarly, studies on the impact of physical activity on RA were also reviewed. Results: The influence of physical activity on serum inflammatory markers in RA patients was limited. Vitamin D supplementation significantly reduced disease activity, alleviated pain, and mitigated methotrexate-related side effects, especially in patients with baseline vitamin D deficiency or lower serum levels. In contrast, other vitamins have not exhibited the same positive effects. These findings underscore the need for continued research to optimize the role of various vitamins in managing RA effectively.